PENTINGNYA PEMAHAMAN AGAMA HINDU DENGAN PUSTAKA SUCI, NALAR, LOGIKA VERSUS MULA KETO: (Sebuah Analisis Teori Kritis) - I Komang Sudharka Utama (UHN IGB Sugriwa Denpasar, 2023)
Religious life, especially Hinduism in Bali, is very strong and strong in terms of rituals or ceremonies, but weak in terms of tattwa (janana) such as theology or philosophy. The reason is his adherence to the adage 'nak mula keto' (that's how it is). So that people just carry out the ritual obligations without the need to ask anything else question its basis for truth. Consequently, most Hindus are relatively